Peranan Sumber Daya Air terhadap Pemanfaatan Ruang Berdasarkan Keseimbangan Tata Air di Wilayah Sub DAS Gajah Wong - Indriyatno, Nowo (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
This reserach is aimed to analyse the condition of water system balance and its role towards the area utilization in Gajah Wong sub catchment region. The method used in this research is by using the analysis of water balance by applying the comparison of the water supply potention and the amount of water required as well as the projection in future and the plan space area. The water supply potention is produced by the surface water and the ground water, while the amount of water required is based on the household activities of the society, agriculture, industry, and socio economic facilities. The result of the analysis will be applied to give a direction towards the terrain utilization. The result of the research in Gajah Wong sub catchment region shows that in 2011 the water supply potention is predicted to keep getting water surplus at the rate 75.691.000 m³/year or seen from the water usage indeks at the rate of 81% at 2011. Therefore, the cistern is predicted to be available to suffice any need. From many researches that have been conducted, the formula proposal on the terrain utilization is more directed to the protection towards the recharge area as well as the preservation and the control towards the water resource. Some of the directions are to stretch the licencing of the land utilization for settlement especially in the recharge area by concidering the slope declivity and the water resource existance.